The territory and the therapeutic itinerary of a user diagnosed with head and neck cancer, Pernambuco, Brazil (Research, Society and Development, 2023)
In view of the need to understand and improve the population's access to healthcare services, especially for the diagnosis of oral lesions and head and neck cancer, this study aims to examine the factors that hinder or facilitate users' entry into the Healthcare Network and the comprehensiveness of care. Methodologically, this study employs a qualitative approach, using the case study category to analyze the therapeutic itinerary of users within the Healthcare Networks. Data were obtained through an interview with a user of the dental clinic service at the Oncology Center of Oswaldo Cruz University Hospital at the University of Pernambuco - CEON/HUOC/UPE. Despite the challenges faced by the user in the diagnosis and care relationship, the understanding of the diagnosis and adherence to treatment were excellent, as was the relationship with the healthcare professionals involved in this process. As a result, it was observed that the therapeutic itinerary proved capable of acting as a tool to facilitate the operationalization of care in the territory, in the more specific context of cancer. Therefore, it is concluded that the therapeutic itinerary can be used to ensure the adoption of measures from the national oncology care policy, guaranteeing universal access to early diagnosis and oncological care, thereby enabling the improvement of prevention, diagnosis, and treatment conditions.